Angular momentum of a rotating dipole - Ahmad, Mohd. Riduan (Universiti Teknikal Malaysia Melaka, 2014)
In this paper, we derive the far field electromagnetic fields of a rotating half-wave dipole antenna. Theoretically, we have demonstrated that the far electromagnetic fields of a rotating half-wave dipole carry angular momentum in the term of φ-φ′, which is absent from the stationary half-wave dipole antenna. The term sin(κr -ωt + [φ -φ′]) tells us that the electromagnetic wave propagates outward with the speed of light c (evidence from k = ω/c) from the dipole along the r axis and both electric and magnetic fields are spinning (oscillate with ω rad/s) and orbiting (rotating with ω0 rad/s) along the r axis with the speed of light. The orbital frequency is evidence from the term φ -φ ′ =ω 0t -ω 0t' =ω 0r /c ·